2022
DOI: 10.3389/fcimb.2022.938608
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Helicobacter pylori infection and gastrointestinal microecology

Abstract: The prevalence of Helicobacter pylori (H. pylori) infection has exceeded 50% worldwide, and it is considered a high-risk factor for chronic gastritis, peptic ulcer, gastric adenocarcinoma, gastroesophageal reflux disease and functional dyspepsia. H. pylori drug resistance is a common problem worldwide. In recent years, the relationship between H. pylori infection and gastrointestinal microecology has received much attention. H. pylori infection changes the structure and composition of gastrointestinal microflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 79 publications
0
19
0
1
Order By: Relevance
“…It also boosts the number of microorganisms in stomach cancer, including nitrate-reducing bacteria, nitrosylobacteria, and E. coli , which promotes nitrate metabolism. The resultant N-nitroso compounds function as carcinogens and promote tumorigenesis[ 72 ]. An increasing body of evidence suggests that H. pylori infection also impacts the intestinal flora.…”
Section: Potential Carcinogenic Effect Of H Pylori ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It also boosts the number of microorganisms in stomach cancer, including nitrate-reducing bacteria, nitrosylobacteria, and E. coli , which promotes nitrate metabolism. The resultant N-nitroso compounds function as carcinogens and promote tumorigenesis[ 72 ]. An increasing body of evidence suggests that H. pylori infection also impacts the intestinal flora.…”
Section: Potential Carcinogenic Effect Of H Pylori ...mentioning
confidence: 99%
“…An increasing body of evidence suggests that H. pylori infection also impacts the intestinal flora. H. pylori invasion of the intestinal mucosa may lead to reduced intestinal permeability[ 72 ] and inhibit E. coli DNA[ 73 ]. H. pylori may also trigger host immune responses, thereby altering the intestinal flora[ 74 , 75 ].…”
Section: Potential Carcinogenic Effect Of H Pylori ...mentioning
confidence: 99%
“…It has been shown that the gut microbiota composition and function can impact the pharmacokinetics and pharmacodynamics of antibiotics, which are a key component of H. pylori eradication therapies. By modulating the gut microbiota, it may be possible to enhance the e cacy of H. pylori eradication therapies and reduce the risk of treatment failure (21). Inhibition of H. pylori growth: Some probiotic strains, such as Lactobacillus and Bi dobacterium, have been shown to produce antimicrobial compounds that can inhibit the growth of H. pylori.…”
Section: The Potential Role Of the Gut Microbiota In H Pylori Eradica...mentioning
confidence: 99%
“…H. pylori is a bacterium characterized by its spiral shape and gram-negative nature, which has a global prevalence, surpassing 50% of the global population, with greater occurrence in developing nations. It is widely recognized as the primary etiological factor responsible for chronic or atrophic gastritis, peptic ulcer, gastric lymphoma, and gastric carcinoma [ 31 ]. Considering its carcinogenic properties, the World Health Organization has classified H. pylori as a grade I carcinogen [ 4 ].…”
Section: Introductionmentioning
confidence: 99%